Political Parties in Indonesia and the Internet: A comparative analysis - Muhammad Sigit Andhi Rahman; Ella S Prihatini (President University, 2019)
This is the first such study of the use of Internet by political parties in Indonesia. It also documents parties’ websites performance index and online popularity for campaigning in 2019. The purpose of this comparative study is to look at how the Internet was used by Indonesian political parties approaching the 2019 elections. Internet campaign consists of two parts: online presence through political party website, and political marketing through social media. Total of 16 parties participating the elections next year were examined for how they are utilizing official websites and social media platforms. We created an index based on list of website features (scoring system) and then classify it into 4 variables (information provision, mobilization, engagement, and technological sophistication) containing 43 features. We also visualise the descriptive statistical analysis on parties’ social media accounts using RStudio software. The study found that despite half of Indonesian national population is using the Internet, political parties were not yet achieving their maximum potential in using the digital media to disseminate political messages and propaganda. The quality of most of the websites have been subpar. In addition, the quality seems to have no relationship with the financial resources and the current parliamentary size of political parties. On average, official social media accounts run by parties has only been used in the last 3.25 years. Well-established older parties in Indonesia continue to engage with their constituents without heavily relying on social media. Yet, this situation is very likely to change in the future as parties’ elites are now beginning to look into this platform as they seek out to the millennials for electoral support.